Verstek Divorce Case in the Perspective of Positive Law and Islamic Law - A. Taufik Taufik (Universitas Islam Sultan Agung, 2020)
The research problem is that, in examining the verstek of the divorce case, the judge asked the plaintiff to prove the argument of the lawsuit with written evidence and / or witnesses, even though the verstek provisions did not regulate that. What is the legal basis of evidence regarding the subject matter in verstek and why did the defendant choose not to attend the trial and how is the verzet examination of divorce cases in court. how to study literature. While the data analysis method used is descriptive normative, that is, the method used to describe the norms on which the judge accepts, examine and resolve cases that emphasize the aspect of the prevailing legislation. Based on the analysis, it can be seen that the reason the judge ordered proof is: In the case of the verstek case of divorce cases, the principle of Lex Specialis Derogat Lex Generali is applied, therefore divorce cases are an exception to the HIR provisions. Because proof can show more of a legal function in providing a sense of justice and protection to society. Proof is useful to know the truth of the plaintiff's claim whether the lawsuit has legal grounds and does not violate rights. The formulation of Article 125 paragraph (1) HIR does not contain the words 'must', but instead the word 'accepted' is used.Apart from basing it on positive legal provisions, in the version of divorce cases, the panel of judges also based on the doctrine in the Fiqh Books in the form of syar'iyah evidence. In a divorce case what is sought is material truth, not mere formal truth. It can be seen from the verdicts in divorce cases both recognized and in the verstek verdict, still undergoing a proving process. Both positive law and Islamic law see the need for proof in a verdict from a divorce case.Keywords : Verstek; Divorce Case; Positive Law; Islamic law.